Transversal-readout architecture for CMOS active pixel image sensors. - Miyatake, S. (IEEE Transactions on electron devices)
Novel architecture for CMOS active pixel image sensors (APSs), which eliminates the vertically striped fixed pattern noise (FPN), is presented. There are two kinds of FPN for CMOS APSs. One originates from the pixel-to-pixel variation in dark current and source-follower threshold voltage, and the other from the column-to-column variation in column readout structures. The former may become invisible in the future due to process improvements. However, the latter, which results in a vertically striped FPN, is and will be conspicuous without some subtraction because of the correlation in the vertical direction. The pixel consists of a photodiode, a row- and column-reset transistor, a source-follower input transistor, and a column-select transistor instead of the row-select transistor found in conventional CMOS APSs. The column-select transistor is connected to a signal line that runs horizontally instead of vertically. An experimentally fabricated 320×240-pixel CMOS APS employing the transversal-readout architecture exhibited neither vertically nor horizontally striped FPN. A buried-photodiode device with the transversal-readout architecture is also proposed.